Utilização da termografia para detecção do fenômeno de Raynaud secundário - Viana, Janaina de Fatima Ricci (2020)
Raynaud’s phenomenon (RP) is a clinical manifestation characterized by a transient ischemic process in an exaggerated vascular response to cold, stress and vibrational mechanisms. It can be classified as primary RP, of idiopathic character, without association with any underlying disease and with milder symptoms and secondary (RP2) being a typical sign for patients diagnosed with Systemic Sclerosis (Ssc), an autoimmune rheumatic disease of the connective tissue , of heterogeneous character, with multisystemic involvement. Among the various resources for the verification of vascular impairments, thermography is a method applied to support the diagnosis of these changes. The objective of this study was to use three different metrics to calculate the Distal Dorsal Difference (DDD) (minimum DDD, maximum DDD and the sum of DDD’s of all fingers) in thermographic images to analyze the thermal behavior both in healthy individuals and in individuals with RP2. The research was carried out from 2018 to 2019. The sample consisted of 44 individuals in a control group (CG) and 44 individuals corresponding to the group with ES (RP2). The participants, after acclimatizing for 10 minutes, were submitted to the cold stress test protocol, which consisted of immersing their hands in a water container at a temperature of 15°C for 60 seconds. The acquisition of thermographic images was performed in seven moments: pre-test and in the 1st, 3rd, 5th, 7th, 10th and 15th minute. At each moment, DDD values (from all fingers – minimum, maximum and sum) between groups were analyzed. For statistical analysis, the t-test for independent samples and the Cohen’s d test were used. Regarding the results, there was a significant difference in relation to the rate of temperature recovery between the groups at all times (p = 0.000). The CG showed a rate of reheat just after the first minute following the cold stress test (- 1.48ºC in t1 to -0.03ºC in t3; p = 0.000), while the RP2 group was extremely negative in the first minute after the test (-16.88ºC), as time passed, the rate of temperature recovery became less negative, but at no time did it become positive, even over the fifteen minutes (-7.23ºC). The minimum, maximum DDD and the sum of DDD’s, proved to be a valid index for checking and distinguishing the temperature gradient in the study with individuals identified with or without secondary RP, between the 1st and 5th minute.